Paramagnetic encoding of molecules - Kretschmer, Jan; David, Tomáš; Dračínský, Martin; Socha, Ondřej; Jirak, Daniel; Vít, Martin; Jurok, Radek; Kuchař, Martin; Císařová, Ivana; Polasek, Miloslav (Nature communications, 2022)
Contactless digital tags are increasingly penetrating into many areas of human activities. Digitalization of our environment requires an ever growing number of objects to be identified and tracked with machine-readable labels. Molecules offer immense potential to serve for this purpose, but our ability to write, read, and communicate molecular code with current technology remains limited. Here we show that magnetic patterns can be synthetically encoded into stable molecular scaffolds with paramagnetic lanthanide ions to write digital code into molecules and their mixtures. Owing to the directional character of magnetic susceptibility tensors, each sequence of lanthanides built into one molecule produces a unique magnetic outcome. Multiplexing of the encoded molecules provides a high number of codes that grows double-exponentially with the number of available paramagnetic ions. The codes are readable by nuclear magnetic resonance in the radiofrequency (RF) spectrum, analogously to the macroscopic technology of RF identification. A prototype molecular system capable of 16-bit (65,535 codes) encoding is presented. Future optimized systems can conceivably provide 64-bit (~10^19 codes) or higher encoding to cover the labelling needs in drug discovery, anti-counterfeiting and other areas.
Keywords: Magnetics; Humans; Lanthanoid Series Elements; magnetismus; Magnetic Resonance Spectroscopy; lidé; magnetická rezonanční spektroskopie; lanthanoidy